Rural archaeology in early urban northern Mesopotamia : excavations at Tell al-Raqa'i - Schwartz, Glenn M. (Monumenta archaeologica (Los Angeles, Calif.) ;, 2015)
La 4e de couverture porte : "This book presents a new perspective on the emergence of urban societies in Mesopotamia, focusing attention on life in a rural village and helping to correct the traditional bias by archaeologists toward the urban and the elite. Reporting on the extensive excavations at Tell al-Raqa'i (early-middle 3rd millennium BC) in upper Mesopotamia/Syria, the authors offer detailed studies on architecture, pottery, animal bones, plant remains, and other varieties of artifacts and ecofacts. These data provide a wealth of information on the nature of life in a small community during the transition to urbanism. Spatial and social organization, household economics, and the significance of enigmatic structures such as the Round Building and a small "temple" are among the issues discussed. Artifact The excavations at Raqa'i, with their exposure of a broad segment of an ancient village, reveal important new insights on the nature of rural life in upper Mesopotamia and on the role of villages in early urban societies in general."